Visual detection of a cohesionless crack in rock under three-point bending. (15th April 2019) - Lin, Qing; Wan, Bin; Wang, Siqi; Li, Shiyuan; Fakhimi, Ali
Highlights: Digital image correlation (DIC) is used to obtain the crack opening displacement. Three types of opening displacement patterns help to identify fracture properties. A technique within the framework of cohesive zone model is introduced. The critical crack opening and length of the cohesionless crack are measured. A cohesionless crack is observed to occur at peak load for a notched specimen. Abstract: Crack initiation and propagation in rock involve the development of a nonlinear zone around the crack tip called fracture process zone. The existence of fracture process zone influences the fracture behavior and therefore it must be carefully investigated. This zone is normally idealized as a cohesive zone whose mechanical properties are difficult to measure. In this study, a relatively simple approach is proposed to identify the properties of the cohesive zone and the length of the cohesionless crack in a sandstone specimen under three-point bending. Two types of specimens were tested: beams with center notch and with smooth boundary. The digital image correlation (DIC) was utilized to obtain the opening displacement around the position where the fracture initiated. For a small length of a horizontal section around the specimen center, the material is considered to be in the state of uniaxial tension and its behavior is interpreted by the cohesive zone model. The proposed approach discusses three types of opening displacement distribution patterns (I), (II), (III). Pattern (I) is related to tensile loading of the material, pattern (II) suggests the development of material softening within the cohesive zone and pattern (III) indicates the development of the cohesionless crack. These displacement patterns together with the appropriate reference loadings are used to identify the length of the cohesionless crack. For example, observation of pattern (III) is consistent with the development of the cohesionless crack when the reference loading is the beginning of experiment. Further, the proposed method is useful for measuring the critical crack opening displacement and the fracture energy.